Differentiate responses of tetraploid and hexaploid wheat (Triticum aestivum L.) to moderate and severe drought stress: a cue of wheat domestication. (2nd January 2021) - Gui, Yanwen; Sheteiwy, Mohamed S; Zhu, Shuangguo; Zhu, Li; Batool, Asfa; Jia, Tingting; Xiong, Youcai
ABSTRACT: Differentiate mechanism of wheat species in response to contrasting drought stress gradients implies a cue of its long-term domestication. In the present study, three water regimes including well-watered control (WW, 80% field water capacity (FC)), moderate drought stress (MS, 50% FC, ) and severe drought stress (SS, 30% FC) were designed to reveal different responses of eight wheat species (four tetraploid and four hexaploid) representing different breeding decades and genetic origins to drought stresses. The data indicated that 50% FC and 30% FC fell into the soil moisture threshold range of non-hydraulic and hydraulic root signal occurrence, respectively. In general, grain yield, grain number/spike weight per plant, aboveground biomass, harvest index (HI) and water use efficiency (WUE) were significantly higher in hexaploid species than those of tetraploid species under drought stress ( P < .05). Particularly, non-hydraulic root signal was triggered and continuously operated under 50% FC, while hydraulic root signal was observed under 30% FC, respectively. Under 80% FC, the allometric exponent (ɑ) of Maboveground vs Mroot decreased from tetraploid to hexaploid (both were of <1), indicating that during the domestication, the hexaploid species allocated less biomass to root system. For the relationship of Mear vs Mvegetative, the ɑ value was significantly greater in the hexaploid species, showing that hexaploid wheat distributed more biomass to ear than tetraploid to improve yield. Under 50% FC, this trend was enhanced. However, under 30% FC, there was no significant difference in the ɑ value between two species. Additionally, correlation analyses on yield formation affirmed the above results. Therefore, drought tolerance tended to be enhanced in hexaploid species under the pressure of artificial selection than that of tetraploid species. When drought stress exceeded a certain threshold, both species would be negatively seriously affected and followed a similar mechanism for better survival.